Năm 5 minutes to a great real estate sales meeting - Mayfield, John D.
Every real estate professional knows -- time is money! John Mayfield's Five Minutes to a Great Real Estate Sales Meeting: A Desk Reference for Managing Brokers is a treasure chest of ideas for the real estate broker/manager on how to hold successful and motivational sales meetings. This simple, time-saving tool offers creative and proven ideas and includes a CD-ROM packed with resources that allow brokers and brokerage owners to spend more of their time focusing on day-to-day management duties, as well as listing and selling, rather than meeting preparation